Pembentukan Karakter Tanggung Jawab Siswa pada Pembelajaran Daring Melalui Implementasi Pendidikan Karakter - Sioratna Puspita Sari; Jessica Elfani Bermuli (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
The aim of this study was to describe the process of students’ responsibility building through the implementation of character education in online learning. This research used descriptive qualitative method. The subjects of this study were students of class X IPA consisting of 27 students. Instruments of the research used were data of observation, reflection of every class teaching, lesson plan (RPP) and mentor’s feedback. All of the data were obtained during the implementation of the Field Implementation Program (PPL). The data analysis technique used every result of previous research to support the data findings in the field which were described in a qualitative description. The results of this study indicated that the implementation of character education is the right solution to be able to shape students’ responsibility. The process of character building of students’ responsibility through the implementation of character education is carried out in a holistic and integrated manner through providing motivation, class regulations, delivery of subject matter, group discussions and reflection activities. The character building of students’ responsibility is carried out optimally covering all aspects of students, namely cognitive, affective and psychomotor.